Consensus Definition and Prediction of Complexity in Transurethral Resection or Bladder Endoscopic Dissection of Bladder Tumours - Roumiguié, Mathieu; Xylinas, Evanguelos; Brisuda, Antonin; Burger, Maximillian; Mostafid, Hugh; Colombel, Marc; Babjuk, Marek; Palou Redorta, Joan; Witjes, Fred; Malavaud, Bernard (Cancers, 2020)
Ten senior urologists were interrogated to develop a predictive model based on factors from which they could anticipate complex transurethral resection of bladder tumours (TURBT). Complexity was defined by consensus. Panel members then used a five-point Likert scale to grade those factors that, in their opinion, drove complexity. Consensual factors were highlighted through two Delphi rounds. Respective contributions to complexity were quantitated by the median values of their scores. Multivariate analysis with complexity as a dependent variable tested their independence in clinical scenarios obtained by random allocation of the factors. The consensus definition of complexity was "any TURBT/En-bloc dissection that results in incomplete resection and/or prolonged surgery (>1 h) and/or significant (Clavien-Dindo ≥ 3) perioperative complications". Logistic regression highlighted five domains as independent predictors: patient's history, tumour number, location, and size and access to the bladder. Receiver operating characteristic (ROC) analysis confirmed good discrimination (AUC = 0.92). The sum of the scores of the five domains adjusted to their regression coefficients or Bladder Complexity Score yielded comparable performance (AUC = 0.91, C-statistics, p = 0.94) and good calibration. As a whole, preoperative factors identified by expert judgement were organized to quantitate the risk of a complex TURBT, a crucial requisite to personalise patient information, adapt human and technical resources to individual situations and address TURBT variability in clinical trials.
Keywords: transurethral resection; bladder cancer; en-bloc resection